Meglumine-based supramolecular amphiphiles: The effect of chain length - Alonso, J. D. [UNESP]; Ferreira, L. M.B. [UNESP]; Oyafuso, M. H. [UNESP]; Cassimiro, D. L. [UNESP]; Barud, H.; Ribeiro, C. A. [UNESP] (Elsevier, 2022)
Surfactants are amphiphilic substances that lower the surface tension or influence the surfaces' contact between two liquids. They are suitable for a wide range of industrial applications, often being used as emulsifiers. However, most of them are petroleum derivatives and generally are non-biodegradable. New synthetic surfactants have been reported in the literature using a covalent synthesis method, but it takes several steps and uses a large amount of toxic organic solvents. To overcome those drawbacks, we proposed a supramolecular green synthesis route. The acid-base reaction between meglumine (MEG) and two saturated carboxylic acids differing in chain size, undecanoate acid (UM, 11 carbons) and palmitic acid (PM, 16 carbons), were performed in a minimum quantity of organic solvent. The supra-amphiphiles, PM and UM, were analyzed by Nuclear Magnetic Resonance (NMR), Differential Scanning Calorimetry (DSC), Capillarity Viscosity, Small-angle X-ray scattering (SAXS), and Polarized Optical Microscopy (POM) in the presence and/or absence of water. We observed two distinct self-assembly behaviors in water. UM act as a surfactant since SAXS showed micellar aggregation, and its relative viscosity curve has no alteration. Additionally, the events present in DSC curves show no evidence of gel-sol transition due absence of stable hydrogen bonds. On the other hand, PM act as a supramolecular polymer, as evidenced by a baseline shift of the DSC curves due to the disruption of hydrogen bonds. Moreover, PM self-assembles in water in a liquid-crystalline arrangement with increasing viscosity in a concentration-dependent manner. SAXS studies showed the formation of lamellar and hexagonal mesophases. Based on these results, we proposed a model in which the adducts' supramolecular organization is dependent on the hydrophilic/hydrophobic balance. When it tends to the hydrophobic side, there is the formation of the supramolecular polymer. The Van der Waals interactions are necessary to organize the liquid-crystalline mesophase. Also, they are necessary to stabilize the hydrogen bonds between MEG/water, enabling the gel-sol transition, leading to new properties, like thermal reversibility observed in PM.
Keywords: Supra-amphiphiles; Supramolecular chemistry; Supramolecular polymers; Surfactants